Influence of Work-Life Balance, Interpersonal Communication and Work Environment on Job Satisfaction PT. Employee Cooperative. Pupuk Sriwidjaja Palembang - Frecilia Nanda Melvani; Veybitha, Yolanda; Sakarina, Sari; Pamuji, Muhni (International Journal of Management and Business Economics, 2024)
This study endeavors to ascertain the impact of work-life balance, interpersonal communication, and work environment on employee job satisfaction within the PT Pupuk Sriwidjaja Palembang employee cooperative. Employing quantitative methods and survey techniques, this research employs Multiple Linear Regression with SPSS software as the measurement tool. The sample for this study encompasses 40 respondents, who were purposively selected to ensure relevance. The respondents completed the questionnaire online. The research findings indicate that work-life balance, interpersonal communication, and the work environment exert a positive and significant influence on employee job satisfaction at the PT Pupuk Sriwidjaja Palembang employee cooperative, both collectively and individually.